Rational construction of genome-reduced Burkholderiales chassis facilitates efficient heterologous production of natural products from proteobacteria - Liu, Jiaqi (Nat Commun, 2021)
Heterologous expression of biosynthetic gene clusters (BGCs) avails yield improvements and mining of natural products, but it is limited by lacking of more efficient Gram-negative chassis. The proteobacterium Schlegelella brevitalea DSM 7029 exhibits potential for heterologous BGC expression, but its cells undergo early autolysis, hindering further applications. Herein, we rationally construct DC and DT series genome-reduced S. brevitalea mutants by sequential deletions of endogenous BGCs and the nonessential genomic regions, respectively. The DC5 to DC7 mutants affect growth, while the DT series mutants show improved growth characteristics with alleviated cell autolysis. The yield improvements of six proteobacterial natural products and successful identification of chitinimides from Chitinimonas koreensis via heterologous expression in DT mutants demonstrate their superiority to wild-type DSM 7029 and two commonly used Gram-negative chassis Escherichia coli and Pseudomonas putida. Our study expands the panel of Gram-negative chassis and facilitates the discovery of natural products by heterologous expression.